Propuesta para la implementación del Cuadro de Mando Integral como herramienta de gestión de calidad en el Departamento de Talento Humano del Hospital Básico de Saraguro, año 2022 - Salas Guerrero, Stephanie Andreina (2023)
The present research work aims to design a proposal for the implementation of the Balanced Scorecard as a quality management tool in the Human Talent Administration Unit, for this purpose, the problem of the lack of application of a quality management system of this type was detected, which guides the administrative staff of the institution in the search for continuous improvement. In relation to the description above, the research aims to design a proposal as an alternative solution to facilitate decision making through the monitoring of all the parameters of the Administrative Unit and thus generate strategies that imply a favorable radical change within the same, constituting a support to internal management; in turn, its implementation will provide users with a quality service in terms of Human Resources Management by the administrative area. The methodology used for the elaboration of the research proposal called Balanced Scorecard is based on the use of inductive and analytical- synthetic methods, as well as the application of information gathering instruments (semi- structured interview and observation sheet), which allowed gathering relevant information for the elaboration of the proposal; through this type of research it was possible to determine the use of the PESTEL and AMOFHIT tools for the situational diagnosis, as well as the elaboration of a TOWS matrix based on a previous analysis of the external and internal environment of the department, in order to design strategies that can respond to the institutional needs.